An intelligent system for manage the processes of preparation, growing, and harvesting crops in the conditions of hybrid wars - Shvorov, S.; Opryshko, O.; Dudnyk А.; Tsitsyurskii, Y.; Zaloznyi, R. (Energy and Automation, 2024)
The relevance of the work lies in the fact that in the conditions and after the end of the war, many elements of weapons and military equipment remain on agricultural fields. In order to avoid collisions of agricultural machinery with these elements, the following tasks are solved with the help of the proposed system: monitoring of the field based on the use of space and unmanned aerial vehicles, planning of fieldwork, and synthesis of the routes of movement of unmanned tractors and combines, as well as control and operational management of their modes of operation. Based on information from the sensors of space and aircraft using special software, a microrelief of the field is constructed, and the coordinates of dangerous elements (obstacles) in the path of unmanned vehicles are determined. In addition, water erosion of the soil is monitored at this stage. The compromise-optimal routes and movement parameters of unmanned tractors for plowing and fertilizing the land are determined in the second stage. In the third stage, the volume and density of the crop in each field section are specified. The coordinates of obstacles to implementing the compromise-optimal movement trajectories and unmanned harvesters’ optimal speed of movement combine harvesters during harvesting. Key words: intelligent control system, unmanned tractors and combines, monitoring, space and unmanned aerial vehicles